Role of green alder in boreal conifer growth: competitor or facilitator? - Morgane Urli; Nelson Thiffault; Daniel Houle; Sylvie Gauthier; Yves Bergeron (Canadian Science Publishing, 2021)
Sustainable forest management implies successful regeneration after disturbances. Low N availability and competition can, however, limit tree establishment in boreal ecosystems. To develop silviculture strategies that maintain productivity in such context, we established a field trial in northern Québec, Canada. We evaluated if a companion N2-fixing species (Alnus alnobetula) promotes or hinders Picea mariana and Pinus banksiana establishment over six growing seasons. We tested if Alnus has a facilitation effect through nutritional processes and a competition effect through light interception. Foliar stable nitrogen isotope ratio (δ15N = 15N/14N, ‰) results confirmed that Alnus obtains a substantial part of its N through biological fixation and represents an N source in this system. Although we did not observe increased foliar N concentrations in either conifer species in the presence of Alnus, Pinus growth was nonetheless higher in presence of Alnus, whereas no difference was observed for Picea. In the plots where Alnus cohabited with the conifers, the former had a negative impact on seedling growth, suggesting a significant competition for light. Overall, the net effect of Alnus was positive for Pinus and neutral for Picea. Our results have significant implications for silviculture in N-limited systems, especially in the context of climate change that imposes increased levels of stress on regeneration.